2021
DOI: 10.3390/app11062737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limb-Specific Resistance Training on Central and Peripheral Artery Stiffness in Young Adults: A Pilot Study

Abstract: This study aimed to investigate the effect of limb-specific resistance training on arterial stiffness in young adults. Twenty-four participants were randomly assigned to three groups: upper-limb resistance training (n = 8 (URT)), lower-limb resistance training (n = 8 (LRT)), and control group (n = 8 (CON)). Both URT and LRT groups performed the limb-specific resistance training at 70–80% of one-repetition maximum twice a week for 8 weeks. The aortic pulse wave velocity and augmentation index (AIx) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Kim et al [8] determined whether resistance training protocols for upper and lower limbs improve arterial stiffness in healthy young adults, respectively. Their preliminary data found that the resistance training on upper extremities significantly decreased the augmentation index, indicating improved peripheral artery stiffness, and the resistance training on lower extremities showed no significant changes in arterial stiffness.…”
Section: Neuromechanical Motor Rehabilitation Techniquesmentioning
confidence: 99%
“…Kim et al [8] determined whether resistance training protocols for upper and lower limbs improve arterial stiffness in healthy young adults, respectively. Their preliminary data found that the resistance training on upper extremities significantly decreased the augmentation index, indicating improved peripheral artery stiffness, and the resistance training on lower extremities showed no significant changes in arterial stiffness.…”
Section: Neuromechanical Motor Rehabilitation Techniquesmentioning
confidence: 99%